Multi-Representation Approach in Improving 1-Dimensional Kinematics Conceptual Understanding - Muhammad Aminuddin; Zulfikar Salman; Asim; Ani Irawati (Universal Education Jurnal Teaching and Learning, 2024)
This study aims to improve students' understanding of 1-dimensional kinematics concepts through a multi-representation approach. A total of 42 physics teacher candidates participated in this study, which used a one-group pretest-posttest experimental design. The instrument used was 18 multiple-choice questions that included various concept representations, such as mathematical, graphical, tabular, pictorial, and verbal. The results showed a significant increase in students' concept understanding after the application of multi-representation learning. The pretest mean score was 44.44, which increased to 89.81 on the posttest, with an n-gain of 0.81 (high category). The paired sample t-test showed a significant difference between the pretest and post-test (Sig. 2-tailed = 0.000). The multi-representation approach allows students to understand concepts from various points of view, helps reduce misconceptions, and supports various learning styles. However, this study has limitations in the design of feedback and formative assessment, which are important to improve in future research to strengthen the effectiveness of learning.